Réponses

2012-04-29T01:38:52+02:00

1) pour x=-1

 A=(5*-1 +2)(2+1)

   =(-5+2)(3)  -->   A=-3*3 =-9 

2) (5x+2)(2-x)

   a=5x*2+5x*(-x)+2*2+2*(-x)

     =10x-5x²+4-2x

     = 8x-5x²+4

3) pour x=-1

     A=8*(-1)-5*(-1)²+4

       =-8-5+4

       =-13+4

       =-9

2012-04-29T01:50:18+02:00

1) pour x=-1

    A=( 5 x(-1) +2) ( 2-(-1) )

    A=( -5 +2 ) ( 2+1)

    A=-5x2 -5x1 +2x2 +2x1

    A=-10 -5 +4 +2

    A=-15+6

    A=-9 reponse

 

2) A=5x fois 2 +5x fois (-x) +2fois2 +2fois (-1)

    A=10x -5x +4 -2

    A=+5x +2 reponse